Mind-Body Practices for Posttraumatic Stress Disorder. (1st June 2013) - Kim, Sang Hwan; Schneider, Suzanne M.; Kravitz, Len; Mermier, Christine; Burge, Mark R.
Abstract : Background: Mind-body practices are increasingly used to provide stress reduction for posttraumatic stress disorder (PTSD). Mind-body practice encompasses activities with the intent to use the mind to impact physical functioning and improve health. Methods: This is a literature review using PubMed, PsycINFO, and Published International Literature on Traumatic Stress to identify the effects of mind-body intervention modalities, such as yoga, tai chi, qigong, mindfulness-based stress reduction, meditation, and deep breathing, as interventions for PTSD. Results: The literature search identified 92 articles, only 16 of which were suitable for inclusion in this review. We reviewed only original, full text articles that met the inclusion criteria. Most of the studies have small sample size, but findings from the 16 publications reviewed here suggest that mind-body practices are associated with positive impacts on PTSD symptoms. Mind-body practices incorporate numerous therapeutic effects on stress responses, including reductions in anxiety, depression, and anger, and increases in pain tolerance, self-esteem, energy levels, ability to relax, and ability to cope with stressful situations. In general, mind-body practices were found to be a viable intervention to improve the constellation of PTSD symptoms such as intrusive memories, avoidance, and increased emotional arousal. Conclusions: Mind-body practices are increasingly used in the treatment of PTSD and are associated with positive impacts on stress-induced illnesses such as depression and PTSD in most existing studies. Knowledge about the diverse modalities of mind-body practices may provide clinicians and patients with the opportunity to explore an individualized and effective treatment plan enhanced by mind-body interventions as part of ongoing self-care.